Understanding knowledge transfer behavior in Malaysian organizations / Dr. Hairulniza Abd Rahman and Dr. Kardina Kamaruddin - Abd Rahman, Hairulniza; Kamaruddin, Kardina (Universiti Teknologi MARA, Kedah, 2024)
Firms invest their resources considerably to enhance job knowledge for their employees. In return, companies want employees to share what they have learned. Yet despite companies’ attempts to encourage knowledge sharing, many employees withhold what they know a phenomenon known as knowledge hoarding or knowledge hiding. Therefore, the present study aims to understand knowledge transfer behavior (KTB) among employees. This paper reviews the nature of knowledge transfer, knowledge sharing and knowledge transfer behavior. The literature review is conducted to identify the differences between knowledge sharing and knowledge transfer characteristics. The initial discussion in this paper is discussing the nature of knowledge transfer and common practices of knowledge transfer behavior. The finding contributes to the individual and business in understanding the nature of knowledge transfer behavior.